CULTIVATING SUSTAINABLE EMPLOYEE ENGAGEMENT AND WELL-BEING INITIATIVES IN INDONESIAN ORGANIZATIONS: A MULTIFACETED EXAMINATIONOF STRATEGIES, CHALLENGES, AND IMPACT ON ORGANIZATIONAL PERFORMANCE - Kosasih Kosasih; Yuarini Wahyu Pertiwi; Cut Ita Erliana; Defi Irwansyah; Dahlan Abdullah (ADISAM Publisher, 2024)
We provide an overview of the research on cultivating sustainable employee engagement and well-being initiatives in Indonesian organizations. The study aimed to comprehensively examine the strategies employed, the challenges faced, and the impact of these initiatives on organizational performance in the Indonesian context. The research was rooted in a mixed-methods approach, combining qualitative and quantitative methods to understand the subject matter better. Data was collected from surveys, interviews, and organizational records. Stratified random sampling was employed for surveys, while purposive sampling was used for interviews, ensuring a diverse and representative dataset. Our analysis incorporated descriptive statistics and inferential statistical methods, such as regression analysis, for quantitative data. Qualitative data underwent thematic analysis, allowing for the identification of patterns and themes. Integrating both data types enabled triangulation and a more profound insight into the research questions. Ethical considerations were paramount throughout the research, with data treated confidentially and participant identities protected. Informed consent was obtained from all participants, and potential biases or conflicts of interest were transparently addressed. While the mixed- methods approach enriched our understanding, it did pose resource and time constraints. While valuable within the Indonesian context, the findings may not be universally applicable. Additionally, challenges related to data collection, such as participant availability and the completeness of organizational records, were acknowledged. This research contributes to the existing body of knowledge by offering insights into the strategies and impact of sustainable employee engagement and well-being initiatives in Indonesian organizations while shedding light on the challenges faced in implementing such programs.